DETERMINACIÓN DEL HINCHAMIENTO LINEAL EN CORTES DE PERFORACIÓN UTILIZANDO STRAIN GAGES - Diana Carolina Flórez Ardila; Jaime Alberto Loza; Marcela Villamizar Serrano; Zuly Himelda Calderón Carrillo (Revista Fuentes El Reventón Energético, 2011)
The wellbore instability problems generated as a result of the contact between drilling fluid and clay formations have been studied for several years, but the complexity of behavior of argillaceous rocks difficult to study. For this reason, it is important and necessary to propose a possible solution by means of experimental testing using as an instrument of measurement "strain gages" in order to determine the linear swelling of clays in contact with different drilling fluids. The main objective of this study is to propose a methodology based on laboratory tests to determine the linear swelling of the clays in drill cuttings using displacement sensors as the "strain gages."